FORMATION OF AESTHETIC IDEALS IN THE SYSTEM OF EUCLIDEAN GEOMETRY (World Bulletin of Education and Learning, 2025)
This article is devoted to mathematical models of the phenomenon of beauty, studying their connection with the aesthetic ideals of Euclidean geometry. The mathematical analysis of beauty is carried out, in particular, through concepts such as symmetry, proportion, and the golden ratio. The article examines the basic principles of Euclidean geometry and their connection with the phenomenon of beauty through examples. Special attention is also paid to the use of these models in education and practical design.
Keywords: Phenomenon of beauty, mathematical models, Euclidean geometry, aesthetic ideals, symmetry, golden ratio, proportions, visual aesthetics, geometric symmetry, beauty in education.